Job search, occupational choice and learning - Tayyar Büyükbaşaran (Central Bank Review (CBR), 2020)
This paper investigates the labor market consequences of incomplete information about workers' own job searching process and best occupations fitting to them. A search and learning model is provided in order to analyze these effects. In the model, search outcomes relay information about workers' job finding abilities and appropriate occupations suited to them, and workers use this information to infer their types. Our theory explains how search outcomes during unemployment can change the beliefs of workers about their job finding ability and consequently affect their decisions including the occupational choices. Characterization of the model results in a simple value function with reservation level of prior belief property that is similar to reservation wage property. Some interesting facts about both micro and macro data are identified and our model's explanation of these facts is discussed. Particularly, our characterization gives rational for why workers with less experience in searching have (1) longer unemployment duration and (2) higher probability of changing occupation by reemployment, and (3) why shifts in Beveridge curve may be observed. Theory can also be used to (4) explain the discouraged worker phenomenon.
Keywords: 330; Search; Matching; Occupational choice; Learning; Unemployment; Discouraged workers; Beveridge curve